Influence of political knowledge on the perceptions of Bauchi state civil servants towards Nigerian federalism - Ahmad, Aliyu Aisha (2022)
Federalism is a political structure that allows states to unite under a central government to maintain a measure of independence and interdependence. However, in Nigeria, the renewed calls and agitations from diverse sectors for the restructuring of Nigerian federalism has over the years been characterized by numerous inconsistencies and tensions. This further aggravates the fragile unity, peace and political stability of the country. This study was designed to determine the influence of political knowledge on the perceptions of Bauchi state civil servants towards Nigerian federalism. Specifically, the study was conducted to determine the level of political knowledge amongst Bauchi state civil servants and identify the civil servant’s perception on Nigerian federalism, as well as examine the relationship between political knowledge and civil servant’s perception on Nigerian federalism among Bauchi state civil servants. The study further examines most influence of political knowledge factors on the civil servant's perceptions on Nigerian federalism amongst Bauchi state civil servants. The political theory of federalism was used to guide the research process of this current study. In order to achieve the research objectives, the study employed quantitative approach based on survey design. A total of 396 respondents were selected through stratified sampling technique from the accessible civil servant’s population of 96,728 from Bauchi State of Nigeria. Data was collected using a questionnaire. Descriptive statistics such as frequency range and percentages while inferential statistics such as correlation, factor analysis and multiple regressions was used to analyse the data. The study results from the descriptive analysis revealed that the respondents have indicated a high level of political structural knowledge, high level of political factual knowledge and high level of overall political knowledge. Furthermore, the result shows that civil servants in Bauchi state have high level of perception on federalism. The result also shows that there is a significant correlation (p<.000) between political structural knowledge, political factual knowledge as well as overall political knowledge with civil servant’s perception of federalism. The research unveils that, political structural knowledge has a positive and significant influence (p<.000) on respondents’ perception of federalism in Nigeria, with coefficient, weight value of 0.130 and statistically significant at 1% confidence level while political factual knowledge has significant and positive influence (p<.000) on civil servant’sssss perception of Nigerian federalism, with coefficient weight value of 0.500 and statistically significant at 1% confidence level. The findings implies that the higher the political factual knowledge and political structural knowledge, the higher the likelihood of respondent to exhibit good perception about Nigerian federalism. The results of the hypothesis were all supported. However, this study has expanded the body of knowledge in the area of federalism by using political knowledge construct to examine the level of perception of the civil servants regarding Nigerian federalism which can be used in theory development and further debates, as many researches pertaining to political knowledge were basically related to democracy and not federalism. Therefore, the research unveils the importance and most influential political knowledge factors related to Nigerian federalism among the civil servants. Hence, it is recommended that government to design an enlightenment program targeting other civil servants and other population in Bauchi state in order to educate them and enhance their understanding and perception about Nigerian federalism.